Somatic AKT1 mutations cause meningiomas colocalizing with a characteristic pattern of cranial hyperostosis. Issue 10 (23rd August 2016) - Keppler‐Noreuil, Kim M.; Baker, Eva H.; Sapp, Julie C.; Lindhurst, Marjorie J.; Biesecker, Leslie G.
Abstract : Somatic genetic mutations in meningiomas are associated with histologic subtypes, anatomical location, and grade. Concomitant hyperostosis occurs with some meningiomas and the pathogenesis is not well understood. Cranial hyperostosis and meningiomas are common in patients with Proteus syndrome, which is caused by a somatic activating mutation in AKT1 c.49G>A. This same mutation has also been found in 6–9% of sporadic non‐syndromic meningiomas. Sixty‐one patients with Proteus syndrome meeting clinical diagnostic criteria were evaluated at the NIH from 1997 to 2014. Of these 61, 52 had a somatic activating mutation (c.49G>A, p.Glu17Lys) in AKT1 confirmed from affected tissue samples. Photographs, physical examination and/or autopsy, X‐rays, CT, and/or MRI scan of the head were reviewed in 29/52 patients. Of the 29 patients, the most common intracranial tumor was meningioma, all co‐localizing with cranial hyperostosis, and diagnosed at younger ages than typical for isolated, non‐syndromic meningiomas. These patients had progressive cranial overgrowth that consisted primarily of diploic space expansion, and was characterized by unilateral, parasagittal, and frontal bone involvement. We hypothesize that sporadic meningothelial and transitional subtype meningiomas are a forme fruste or microform of Proteus syndrome, and activation of the AKT/PI3K pathway drives hyperostosis in both non‐syndromic, and Proteus‐related meningiomas. © 2016 The Authors. American Journal of Medical Genetics Part A Published by Wiley Periodicals, Inc.